SISTEM INFORMASI PENGELOLAAN PERBAIKAN DAN PENGGANTIAN SUKU CADANG MESIN INDUSTRI DEPARTEMEN STORE ROOM PT CHAROEN POKPHAND INDONESIA - Andi Usri Usman; Ahmad Surahmat; Anggi Reinaldo (Journal of Innovation And Future Technology (IFTECH), 2020)
In the current era of computerization, the computer is the tool used by each user, both individuals and institutions have to support the tasks and functions as well as obtain the required information in a way that easier and faster. Currently the department store room Charoen Pokphand Indonesia Company transaction process of repair and replacement of spare parts is still done manually, resulting data processing each transaction prone to error. The research outlined in this report aims to facilitate each employee Charoen Pokphand Indonesia Company, especially department Store Room in processing the data and monitor to be a good status. Thus the Store Room requires the design of information systems that can produce information quickly, reducing data errors occur, facilitate the search for the items required, so that all the transactions can be done easily. The methodology used for the development of this system is the Waterfall Model and storage of data using SQL Server 2005. With the design of Management Information Systems Repair and Replacement Parts Industrial Engineering Department Store Room is expected later in making applications run smoothly and can be applied in the company. After conducting research and analysis and discussion of the problem , there are some problems and obstacles that can be used as guidelines to improve the existing system so that in making this application program problems and obstacles can be overcome as well as possible to support the company's performance.